2017
DOI: 10.1136/bjsports-2017-097895
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for head injury events in professional rugby union: a video analysis of 464 head injury events to inform proposed injury prevention strategies

Abstract: Article:Tucker, R., Raftery, M., Kemp, S. et ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
135
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(148 citation statements)
references
References 22 publications
12
135
1
Order By: Relevance
“…The chances of a concussion were decreased when the tackler did not move before the tackle event; this result is in line with those of previous studies. 6,10 The risk of concussions 6 and the propensity to cause an HIA 10 were significantly greater among tacklers moving at higher speeds or accelerating. Therefore, we recommend that tacklers control their speed in the pre-contact phase, which results in a tackle characteristic that lowers the risk of concussions at the moment of contact.…”
Section: Factors Reducing the Likelihood Of The Tackler-related Conmentioning
confidence: 98%
See 1 more Smart Citation
“…The chances of a concussion were decreased when the tackler did not move before the tackle event; this result is in line with those of previous studies. 6,10 The risk of concussions 6 and the propensity to cause an HIA 10 were significantly greater among tacklers moving at higher speeds or accelerating. Therefore, we recommend that tacklers control their speed in the pre-contact phase, which results in a tackle characteristic that lowers the risk of concussions at the moment of contact.…”
Section: Factors Reducing the Likelihood Of The Tackler-related Conmentioning
confidence: 98%
“…[3][4][5] Recently, in rugby union, research on the inciting events leading to concussion and head injury assessment (HIA) has increased, 6-10 with a particular focus on tackling situations. 6,[8][9][10] The aforementioned studies assessed professional rugby union players, and it is considered that the results are unlikely to be applicable to nonprofessional cohorts included both youth and community cohorts. 6,9,10 Furthermore, since the HIA is applied to the only professional level, it is easily possible to collect the concussion data and video records compared with community level.…”
Section: Introductionmentioning
confidence: 99%
“…Certain studies also focused on niche areas including head injuries and concussions, 31 40 53-70 spinal and neck injuries, [71][72][73][74][75][76][77][78][79] shoulder injuries, 34 80-88 knee and ankle injuries, [89][90][91][92][93] and the influence of tackle technique on injuries. 61 64 65 69 94-96 Overall and time-loss injury frequencies and rates for rugby union (tables 1 and 2) and sevens (table 3) were tabulated (all injury types included). Tackle-related injury case studies were also summarised for all levels of rugby union and sevens from 1995 to 2018 (see online supplementary appendix 1).…”
Section: Data Interpretationmentioning
confidence: 99%
“…Research on inciting events leading to concussion and HIA with video records has progressed rapidly in recent years [14][15][16][17] . Previous research, targeting the European professional level, suggested there was a higher risk of concussion when the tackler accelerated into a tackle or had head contact with the ball-carrier's head 14,17) . Sobue et al showed that concussion occurred significantly more often during tackles with incorrect head positioning (i.e.…”
Section: Introductionmentioning
confidence: 99%